Implementation of Control System and Tracking Objects in a Quadcopter System - Ariram, Siva; Röning, Juha; Kowalczuk, Zdzisław (Interactive Collaborative Robotics, 2019)
In this paper, we implement a quadcopter assembly with control and navigation module. The project also includes the design of the control panel for the operator which consists of a set of the microcontroller and the glove equipped with sensors and buttons. The panel has a touch screen which displays current parameters such as vehicle status, including information about orientation and geographical coordinates. The concept of quadcopter control is based on the movement of the operator hand. In addition, we have included the object detection for detecting the objects from the quadcopter view of point. To detect an object, we need to have some idea of where the object may be and how the image is divided into segments. It creates a kind of chicken and egg problem, where we must recognize the shape (and class) of the object knowing its location and recognize the location of the object knowing its shape. Some visual characteristics such as clothing and the human face, they can be part of the same subject, but it is difficult to recognize this without recognizing the object first.